Implementation of Finite State Machine as an Alternative Story in Another World Reborn Game - Marlina; Wilbert Nickson Winarto; Ahyar Muawwal (KHARISMA Tech, 2026)
The development of RPG (Role Playing Game) games requires dynamic interactions and immersive stories. However, Another World Reborn has weaknesses in terms of monotonous NPC (Non-Player Character) behavior and a linear storyline, thus reducing the level of replayability. This study aims to implement the Finite State Machine (FSM) method to create a dynamic alternative story using RPG Maker MV. FSM is applied to organize NPC state transitions, dialogue branches, and storylines based on player choices, resulting in three alternative endings: (A) defeating the Demon King, (B) siding with the Devil, and (C) returning to the original world. Testing using Black Box Testing shows that all features function as designed, while usability testing with the System Usability Scale (SUS) on 20 respondents resulted in a score of 74.3 (Acceptable category), indicating a significant improvement from the initial version (score 61.1). And for the reason for choosing 20 respondents is based on the principle that this number is sufficient to identify the majority of usability problems without requiring large resources. Furthermore, these numbers allow for simple statistical analysis, such as the mean and standard deviation, which are useful for measuring the consistency of user experiences. The research results demonstrate that FSM successfully generates three alternative endings while also effectively increasing NPC interactivity and game replayability.